Histomorphological pattern of lesions of cystoscopic bladder biopsies in a tertiary center in Nepal- A retrospective descriptive study - Amar Narayan Shrestha; Anil Regmi; Abilasha Rana; Sony Ghimire; Pragya Karki; Sajina Thapa; Amit Shrestha; Rewant Singh (Journal of Pathology of Nepal)
Background: Bladder cancer accounts for 3% of all cancer diagnoses and is one of the most common cancers worldwide. Bladder tumors have different subtypes and behavioral patterns. This study is performed in the pathology department of Shree Birendra Hospital. It is a data review done on cystoscopic bladder biopsy results for the past 5 years to study the histomorphological patterns of various bladder lesions.